Electronic Payment in Interbank Settlement in Bangladesh: : An Empirical Study of its Adoption and Forecasting using the ARIMA Model - Podder, Bhaskar (Otoritas Jasa Keuangan, 2026)
For over a decade, the Bangladesh government, regulators, and commercial banks have been investing in the Electronic Payment and Settlement System (EPSS) to accelerate economic development, ensure financial stability, and promote financial inclusion. This study examines the adoption of EPSS in Bangladesh and forecasts its trend. The focus is specifically on a component of EPSS – the Real Time Gross Settlement (RTGS). We analyse the historical trend of EPSS and its traditional substitute in detail. The Box-Jenkins methodology is employed to develop an appropriate autoregressive integrated moving average (ARIMA) model for forecasting the increasing share of EPSS in Bangladesh. Our findings reveal that the share of EPSS will be 93.20% and 57.75% with respect to amount and number, respectively, after about three years. The adoption of EPSS with respect to amount shows a steeper upward trend than its adoption with respect to number. Because RTGS adoption is limited to a certain threshold, the number of small-amount transactions is still captured by traditional substitutes. A pervasive lack of digital financial literacy among a subset of the population also drives the adoption of traditional substitutes. Unlike prior works on digital adoption that are based almost exclusively on consumers’ perceptions, this study is grounded in actual data to investigate the adoption of EPSS and its forecasted trend at a country level. It highlights the effectiveness and shortcomings of EPSS in the context of an emerging economy. Our findings can assist policymakers in formulating strategic decisions for the adoption of electronic payment systems in emerging economies.